2021
DOI: 10.1007/s40489-021-00276-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Synchrony in Autism: a Systematic Review

Abstract: Temporal synchrony is the alignment of processes in time within or across individuals in social interaction and is observed and studied in various domains using wide-ranging paradigms. Evidence suggesting reduced temporal synchrony in autism (e.g. compared to neurotypicals) has hitherto not been reviewed. To systematically review the magnitude and generalisability of the difference across different tasks and contexts, EBSCO, OVID, Web of Science, and Scopus databases were searched. Thirty-two studies were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…In support of this three-way relationship between sensory perception, motor function and temporal processing, individuals with ASD experience a variety of sensory difficulties associated with processing (Beker et al, 2017 ; Tavassoli et al, 2014 ), integration (Brandwein et al, 2012 , 2015 ; Russo et al, 2010 ; Stevenson et al, 2014a , b ), and binding (Brock et al, 2002 ; Foss-Feig et al, 2010 ; Greenfield et al, 2015 ; Zhou et al, 2018 ), as well as motor deficits (Bhat et al, 2011 ; Calhoun et al, 2011 ; Cascio et al, 2012 ; Fournier et al, 2010a , b ; Rinehart et al, 2006 ). These motor deficits extend to sensorimotor synchronization, with ASD participants showing higher sensorimotor synchronization variability compared with non-ASD participants (Morimoto et al, 2018 ; Murat Baldwin et al, 2021 ). Further, it has been suggested that individuals with ASD may have deficits in temporal synchrony (Murat Baldwin et al, 2021 ), temporal processing, and temporal perception (Allman, 2011 ; Allman et al, 2011 ; Casassus et al, 2019 ; Stevenson et al, 2016 ), and experience difficulty in detecting temporal changes in sensory stimuli (Brodeur et al, 2014 ; Falter et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this three-way relationship between sensory perception, motor function and temporal processing, individuals with ASD experience a variety of sensory difficulties associated with processing (Beker et al, 2017 ; Tavassoli et al, 2014 ), integration (Brandwein et al, 2012 , 2015 ; Russo et al, 2010 ; Stevenson et al, 2014a , b ), and binding (Brock et al, 2002 ; Foss-Feig et al, 2010 ; Greenfield et al, 2015 ; Zhou et al, 2018 ), as well as motor deficits (Bhat et al, 2011 ; Calhoun et al, 2011 ; Cascio et al, 2012 ; Fournier et al, 2010a , b ; Rinehart et al, 2006 ). These motor deficits extend to sensorimotor synchronization, with ASD participants showing higher sensorimotor synchronization variability compared with non-ASD participants (Morimoto et al, 2018 ; Murat Baldwin et al, 2021 ). Further, it has been suggested that individuals with ASD may have deficits in temporal synchrony (Murat Baldwin et al, 2021 ), temporal processing, and temporal perception (Allman, 2011 ; Allman et al, 2011 ; Casassus et al, 2019 ; Stevenson et al, 2016 ), and experience difficulty in detecting temporal changes in sensory stimuli (Brodeur et al, 2014 ; Falter et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…These motor deficits extend to sensorimotor synchronization, with ASD participants showing higher sensorimotor synchronization variability compared with non-ASD participants (Morimoto et al, 2018 ; Murat Baldwin et al, 2021 ). Further, it has been suggested that individuals with ASD may have deficits in temporal synchrony (Murat Baldwin et al, 2021 ), temporal processing, and temporal perception (Allman, 2011 ; Allman et al, 2011 ; Casassus et al, 2019 ; Stevenson et al, 2016 ), and experience difficulty in detecting temporal changes in sensory stimuli (Brodeur et al, 2014 ; Falter et al, 2012 ). As individuals with ASD often have differences in cerebellum function (D'Mello & Stoodley, 2015 ; Mosconi et al, 2015 )—a crucial neural region involved in subsecond and suprasecond timing mechanisms and motor control (Bijsterbosch et al, 2011 ; Grondin, 2010 ; Rao et al, 2001 )—this difficulty with temporal perception and processing may be related to activity in the cerebellum.…”
Section: Methodsmentioning
confidence: 99%
“…Children and adolescents with autism (including high functioning autism, HFA) display reduced or atypical synchrony in conditions rating both individual motor timing and SMS (meta-analyses: Baldwin et al, 2021;McNaughton and Redcay, 2020 * ).…”
Section: Autism and Synchronymentioning
confidence: 99%
“…There is a slowly growing body of empirical evidence suggesting that effective targeting of temporal synchrony is a mediating factor within varied therapeutic interventions with young children with autism (with, and without LD) (Wimpory et al, 1995(Wimpory et al, , 2007Landa et al, 2011;Pickles et al, 2015;Srinivasan et al, 2015;Dvir et al, 2020;Forti et al, 2020;Griffioen et al, 2020;Whitehouse et al, 2021). Metaanalyses conclude the early primacy of synchrony challenges in autism (including HFA), yet cite the lack of focused therapies (Bloch et al, 2019;McNaughton and Redcay, 2020 * ;Baldwin et al, 2021).…”
Section: Autism and Synchronymentioning
confidence: 99%
“…Nonetheless, all three, diachronic thinking, retrospective memory, and prospective memory, were found to have weaknesses in children with ASD regardless of intellectual capacities. Furthermore, a systematic research review 51 revealed individuals with ASD exhibit mostly temporally asynchronous behaviours when tasks demanded integration of modalities: audio-visual, audio-motor, visuo-tactile, visuo-motor, social motor, and conversational synchrony (diminished synchronisation in spontaneous and intentional interpersonal synchrony, and gesture performance). In effect, research confirmed 52 that auditory temporal processing for rapid signals associated with language processing are impaired in children with ASD.…”
Section: Introductionmentioning
confidence: 99%